Perspectives of Lesson Study Implementation in Deep Learning: A Systematic Literature Review - Rejeki, Sri Rejeki; Nurin Rochayati; Siti Sanisah; Noel Jimbai Balang; Wahyu Azwar; Rihal Jayadi (Journal of Learning Improvement and Lesson Study, 2025)
The research aims to describe and synthesize previous research findings, analyze the relevance of lesson study to the achievement of deep learning, identify the benefits and challenges of its implementation and provide evidence-based recommendations for the development of lesson study that is more effective in supporting the 21st century learning paradigm. The researcher used the SLR (System Literature Rivew) method to review previous studies from the last 10 (2015-2025) years. Journal searches were conducted by researchers through journal provider databases such as Google Scholar (scholar.google.com) and Scopus. The focus of research data is journals with lesson study implementation in deep learning as many as 40 journals indexed SINTA (National) and Scopus (International) from various publishers or journal publishers. The result of this research is that lesson study is an effective collaborative framework in encouraging active and reflective engagement of learners while improving teacher professionalism in improving deep learning.